Commitment and Job Satisfaction with Nurse Job Performance - Aminuddin Aminuddin; A. Suyatni Musrah; Lumastri Ajeng Wijayanti; Yofa Anggriani Utama; Suprapto (Universitas STRADA Indonesia, 2023)
Background: Providing quality nursing services cannot be separated from human resources, which produce good performance and achievements so that they can provide excellent service. Purpose: Knowing the commitment and job satisfaction to nurses' job performance. Methods: Analytical descriptive research design with a cross-sectional approach. Sampling is total sampling. Univariate, and bivariate, uji chi square. Results: The distribution of respondents based on work commitment factors showed that almost all implementing nurses had good commitments, 90.9%. The job satisfaction factor shows that the implementing nurse with good job satisfaction is 59 1%. The chi-square test shows nurses' commitment with a p-value = 0.04 and nurse satisfaction p-value = 1.000, with a value of ? = 0.05. Conclusion: It can be concluded that a da relationship between commitment and the work performance of the implementing nurse, and there is no relationship between job satisfaction and the work performance of the implementing nurse. The hospital's recommendation is to maintain existing commitments by keeping nurses engaged by provoking nurses to participate in making decisions so that nurses feel like a whole part of the hospital.